Let this voice be heard: Anthony Benezet, father of Atlantic abolitionism - Jackson, Maurice (University of Pennsylvania Press, 2009)
A life of conscience -- The early Quaker antislavery movement -- An antislavery intellect develops -- Visions of Africa -- Building an antislavery consensus in North America -- Transatlantic beginnings and the British antislavery movement -- Benezet and the antislavery movement in France -- African voices -- Epilogue: Anthony Benezet's dream